Pemanfaatan Tiktok sebagai Inovasi Media Pembelajaran PAI di Abad 21 - Farihatul Ismaniyah; Imam Syafi’i; Muhammad Fahmi; Muhammad Thohir (La-Tahzan: Jurnal Pendidikan Islam, 2025)
The development of information technology in the digital era has significantly impacted education, including Islamic Religious Education (PAI). TikTok, as a popular social media platform among the younger generation, holds potential as an innovative learning medium. This study aims to analyze the utilization of TikTok in PAI learning using a literature review method. The findings indicate that TikTok can enhance students' interest and understanding of religious materials through concise, creative, and interactive content delivery. The platform also supports independent learning and fosters 21st-century skills such as critical thinking and collaboration. However, challenges include the need for digital literacy, video duration limitations, and the risk of exposure to inappropriate content. Therefore, strategies involving teacher training, ethical guideline development, and strengthening digital literacy are essential to ensure the effective and Islamic-aligned use of TikTok. Keywords: TikTok, PAI Learning, Digital Innovation, Digital Literacy, Social Media.